Pengaruh Iklim Organisasi dan Motivasi terhadap Kinerja Pegawai melalui Organizational Citizenship Behavior - Muhammad Arif Susilo; Jufrizen Jufrizen; Hazmanan Khair (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
The purpose of this study was to determine and analyze the influence of organizational climate on employee performance, the effect of work motivation on employee performance, the effect of organizational climate on OCB, the effect of work motivation on OCB, the effect of OCB on employee performance, the influence of organizational climate on employee performance through OCB, and the effect of work motivation on employee performance through OCB. This research uses associative research with a sample of 66 respondents who are employees of BPSDM North Sumatra Province. Data collection techniques using interviews and a list of statements such as questionnaires and data analysis techniques using Partial Least Square (SmartPls) to test the seven hypotheses proposed in this study. The results of the research show that organizational climate has a significant effect on employee performance, work motivation has a significant effect on employee performance, the organizational climate has a significant effect on OCB, work motivation has a significant effect on OCB, OCB has a significant effect on employee performance, the organizational climate does not affect employee performance through OCB. (In other words, OCB does not act as a mediator), work motivation does not affect employee performance through OCB (In other words, OCB does not act as a mediator).